In vitro testing of an intra-ventricular assist device. (1st October 2019) - Zhu, Shidong; Luo, Lin; Yang, Bibo; Li, Xinghui; Ni, Kai; Zhou, Qian; Wang, Xiaohao
Abstract: A novel pulsatile assist device, intra-ventricular assist device, was proposed to address various disadvantages existing in conventional pulsatile assist device, such as the large size, accessories and reduced pulsatility. The assist device was designed, fabricated and implanted into the sac from left ventricular apex in a home-designed mock circulatory system. In vitro test was carried out and results demonstrated that the response time did not vary with the heart rate, and co-pulsatiled synchronously with native heart by electrocardiograph. The key parameter, stroke volume of proposed device was precisely measured under different afterloads (60, 80, 100, and 120 mmHg), drive pressure (from 90 to 300 mmHg at 30 mmHg intervals), and heart rate (45–150 beats per minute). The measurement results revealed that the output characteristics of device, stroke volume increased with increasing drive pressure but decreased with increasing peripheral resistance, were consistent with the native heart. The proposed pump was then coupled with mock system that was set to a heart failure mode and the circulatory responses were tested. Results showed that the device improved left ventricular pressure from 106 to 158 mmHg, and stroke volume from 25.5 to 44 ml at 90 bpm.